Analysis of quality control in efforts to reduce the level of product defects at PT. MAG - Azmi, Isna Zulfa; Oktora Yogi Sari (Technium Social Sciences Journal, 2020)
The increasing number of bag factories throughout Indonesia that have well-known brands and every manufacturer is required to provide products of good quality. Poor product quality will cause consumers to move to other similar products. So in the production of bags, the thing that must be considered by the company is the quality of its products. In this study the authors aim to analyze quality control in a production process and identify several factors that cause disability in the product, PT. MAG is a bag company that is demanded to control the quality of the production process. This study uses a six sigma analysis tool consisting of five steps, namely using the DMAIC method (Define, Measure, Analyze, Improve, and Control). Based on the results of the study there are three types of disabilities in the production process, including cutting, zippers and broken bag straps with an average sigma value of 2.48 with a DPMO value of 20256.92. Factors affecting the production process are human, machine, environment, equipment, raw materials, and methods. In this case the company can use the Six Sigma method because it is still in the medium category.